Impact of the nutritional status of children with congenital heart diseases on the early post-operative outcome - Sameh R. Ismail; Akhter Mehmood; Noura Rabiah; Riyadh M. Abu-sulaiman; Mohamed S. Kabbani (SpringerOpen, 2021)
Abstract Background Children with congenital heart disease (CHD) frequently become malnourished due to many factors including hypermetabolic state, inadequate caloric intake, malabsorption, and fluid restriction as part of the hemodynamic intervention. The abnormal nutritional status may affect early outcome after pediatric cardiac surgery; we aim to prove the importance of nutritional assessment and patient nutritional preparation before performing pediatric cardiac surgery. Results We conducted a prospective observational cohort study from March 2013 till January 2015. All children from birth until 14 years of age admitted to the pediatric cardiac intensive care unit (PCICU) after cardiac surgery. Nutritional status was assessed preoperatively and prognostic nutritional index (PNI) was calculated. All post-operative outcome parameters, PCICU and hospital length of stay (LOS), ventilation time, the rate of infection, and ICU mortality were recorded. Two hundred fifty-nine children were evaluated. At admission, 179 patients (69%) had intake less than 50% of the recommended daily allowance (RDA) of calories intake. There was a statistically significant relationship between pre-admission RDA and the infection rate (P value 0.018). Severely malnourished patients had significantly longer ICU length of stay (LOS) (P value = 0.049). Similarly, weight and height percentiles have a significant effect on ICU LOS (P value 0.009 and 0.045) respectively. There was a significant relation between PNI ≥ 55 and the ICU LOS (P < 0.05), and ventilation time (P = 0.036). Delay in feeding postoperatively was associated with a higher risk of infection (P = 0.005), and higher mortality (P = 0.03). Conclusions Children with CHD were significantly malnourished preoperatively and had further weight loss postoperatively. Preoperative nutritional status and delayed postoperative enteral feeding were associated with a higher infection rate and mortality.